Peningkatan Motivasi Belajar Siswa Muatan PPKN Menggunakan Model Pembelajaran Problem Based Learning Kelas III SD Negeri Kotagede 4 - Ully Salamah Haryani (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2021)
Based on observation at SD Negeri Kotagede 4, it was found that the students' learning motivation in Civic Education was low, one of the efforts to solve this problem was needed to do a research which used a problem based learning model. The purpose of this research was to increase students' learning motivation in Civic Education using a problem based learning model at SD Negeri Kotagede 4. This research was conducted at SD Negeri Kotagede 4. The subject of this research were 29 students of 3rd grade at SD Negeri Kotagede 4. The data collection techniques used were observation, questionnaires, and documentation. The research instrument was a questionnaire sheet. The data of this research were analyzed by descriptive-qualitative and descriptive-quantitative method. The results of the research using a problem based learning model in the first cycle obtained an average value of 73.41% with a sufficient category. While in the second cycle the average student motivation increased to 83.71% with a good category. In conclusion, the application of the problembased learning model can increase the learning motivation in Civics Education by 3rd grade students at SD Negeri Kotagede 4. Keywords: learning motivation, problem based learning model, Civic Education.